PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 002 TELUK MERBAU KECAMATAN KUBU - Maslinda Maslinda; Lazim. N Lazim. N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is to learn science is still low, the teacher uses conventional learning where students are placed as an object of study as a passive recipient of information. Students just listen penjelasn teachers, students fear response to the lessons, due to fear of punishment. This is evident from the data collection instrument using obseravasi sheet student activity and teacher activity during the learning process takes place in class III SDN 002 Teluk Merbau Kubu district. It can also be seen in the percentage of test scores of students who reach KKM (Minimum Criteria for completeness) in class III SDN 002 Teluk Merbau Kubu district is 35.00% of the 20 students with an average value was 61.85. The school is defined KKM 70. Of these problems is necessary to study a class action by applying inquiry learning model. This study aims to determine whether the application of this inquiry learning model can improve learning outcomes IPA third grade students of SDN 002 Teluk Merbau Kubu district academic year 2014/2015 the number of students 20 students. This research was conducted in two cycles, the first cycle consists of 2 meetings with one daily tests, cycle II also consists of 2 meetings with one daily tests. Data collection instruments in this study is observation sheet student activities, teacher observation sheet activities and daily tests. The percentage of student activity in the first cycle an average of 68.75%, the average cycle II 85.41%, then the percentage of the activity of teachers in the first cycle an average of 72.92% and increased in the second cycle an average of 87.5 %. The percentage of completeness on the basis of a score 35.00% with an average of 61.85 increased to 75.00% with an average 70,00 in the first cycle, then increase again in the second cycle into 90.00% with an average of 80, 00. From these explanations it can be concluded that through the implementation of inquiry learning model can improve student learning outcomes Class III SDN 002 Teluk Merbau Kubu district. Keywords: Inquiry Learning Model, Science Learning Outcomes